Novelties in the roadside flora of Moravia and Silesia (Czech Republic) – 1. Spergularia media - Kocián Petr (Acta Musei Silesiae: Scientiae Naturales, 2015)
The paper reports on a find of the short-lived perennial halophyte Spergularia media on the D1 motorway in NE Moravia, which is the second known record from motorways in the Czech Republic. Possible ways of introduction are shortly discussed.